3D Oral and Cervical Tissue Models for Studying Papillomavirus Host-Pathogen Interactions - Jackson, Robert; Maarsingh, Jason D; Herbst-Kralovetz, Melissa M; Van Doorslaer, Koenraad (Current protocols in microbiology (Online), 2020)
Human papillomavirus (HPV) infection occurs in differentiating epithelial tissues. Cancers caused by high-risk types (e.g., HPV16 and HPV18) typically occur at oropharyngeal and anogenital anatomical sites. The HPV life cycle is differentiation-dependent, requiring tissue culture methodology that is able to recapitulate the three-dimensional (3D) stratified epithelium. Here we report two distinct and complementary methods for growing differentiating epithelial tissues that mimic many critical morphological and biochemical aspects of in vivo tissue. The first approach involves growing primary human epithelial cells on top of a dermal equivalent consisting of collagen fibers and living fibroblast cells. When these cells are grown at the liquid-air interface, differentiation occurs and allows for epithelial stratification. The second approach uses a rotating wall vessel bioreactor. The low-fluid-shear microgravity environment inside the bioreactor allows the cells to use collagen-coated microbeads as a growth scaffold and self-assemble into 3D cellular aggregates. These approaches are applied to epithelial cells derived from HPV-positive and HPV-negative oral and cervical tissues. The second part of the article introduces potential downstream applications for these 3D tissue models. We describe methods that will allow readers to start successfully culturing 3D tissues from oral and cervical cells. These tissues have been used for microscopic visualization, scanning electron microscopy, and large omics-based studies to gain insights into epithelial biology, the HPV life cycle, and host-pathogen interactions. © 2020 Wiley Periodicals LLC. Basic Protocol 1: Establishing human primary cell-derived 3D organotypic raft cultures Support Protocol 1: Isolation of epithelial cells from patient-derived tissues Support Protocol 2: Growth and maintenance of primary human epithelial cells in monolayer culture Support Protocol 3: PCR-based HPV screening of primary cell cultures Basic Protocol 2: Establishing human 3D cervical tissues using the rotating wall vessel bioreactor Support Protocol 4: Growth and maintenance of human A2EN cells in monolayer culture Support Protocol 5: Preparation of the slow-turning lateral vessel bioreactor Support Protocol 6: Preparation of Cytodex-3 microcarrier beads Basic Protocol 3: Histological assessment of 3D organotypic raft tissues Basic Protocol 4: Spatial analysis of protein expression in 3D organotypic raft cultures Basic Protocol 5: Immunofluorescence imaging of RWV-derived 3D tissues Basic Protocol 6: Ultrastructural visualization and imaging of RWV-derived 3D tissues Basic Protocol 7: Characterization of gene expression by RT-qPCR.